Exploration of methods used to describe bacterial communities in silage of maize (Zea mays) cultivars - L. Brusetti; S. Borin; A. Rizzi; D. Mora; C. Sorlini; D.G. Daffonchio (EDP sciences, 2008)
Different techniques to assess bacterial community structure and diversity were evaluated in silages prepared with four different maize cultivars, three conventional and one transgenic (cv. Tundra, event Bt-176). Plants were cultivated in the greenhouse and harvested after 30 days of growth. Silage samples were collected at successive times during fermentation and analyzed for bacterial counts and by various DNA-based fingerprinting techniques. Bacterial counts were similar between cultivars for the total culturable bacteria, sporeforming, and mesophilic and thermophilic lactic acid bacteria (LAB). Further analysis of the species composition of 388 LAB strains by intergenic transcribed spacer (ITS) PCR followed by sequencing of 16S rRNA gene did not reveal differences between cultivars. In contrast, molecular fingerprinting methods targeting whole bacterial communities, such as automated ribosomal intergenic spacers analysis (ARISA) and 16S rRNA gene length heterogeneity-PCR (LH-PCR), indicated that different maize silage batches or cultivars hosted different bacterial communities. Thus, ARISA and LH-PCR fingerprinting techniques offer a fast and sensitive method to compare bacterial communities, and to detect differences in silage bacterial communities.